Etiological Agents of Acute Meningo-Encephalitis Syndrome: Study of 75 Cases in Rajshahi Medical College Hospital - Begum, N; Salam, MA; Rahman, MI; Akter, L; Asafudullah, SM; Mahmood, I; Ahmed, I (TAJ: Journal of Teachers Association, 2009)
Acute meningoencephalitis syndrome (AMES) is a life threatening condition of all ages caused by different microbial agents. Etiological diagnosis is imperative for introduction of appropriate antimicrobial agents to treat the condition. This cross sectional prospective study included seventy five (75) clinically suspected patients of AMES of different age and sex groups, who were admitted at Rajshahi Medical College Hospital (RMCH) during August, 2005 to Jun e, 2006. Cerebra spinal fluid (CSF) was studied by Gram-stained smear examination, bacterial culture, latex agglutination test (LAT), cytological and biochemical tests. The serum samples were also tested for qualitative C - reactive protein (CRP} by latex agglutination test and lgM anti body against Japanese Encephalitis (JE} virus by Enzyme-linked immunosorbent assay (ELISA). Direct microscopy on Gram-stained smears of CSF was found positive for 10 (13.33%) cases while bacterial culture was positive in 17(22.66%) cases. Culture yielded H. influenzae, S. pneumoniae N. meningitidis and Esch. coli in 07 (41.17%), 05 (29.41%), 04 (23.53%) and 01(5.88%) cases respectively. Higher rate of isolation was noted among 0-5 years age group. Out of 75 CSF samples, LAT could be done for randomly selected 45 cases with positive results observed in 18 (40%) cases. Good correlation of increase total white cell count and protein level and decrease glucose level was observed among culture-positive cases in cytological and biochemical analysis of CSF. Serum CRP was found positive in 21 (28.00%) cases and it had also excellent (94.11%) correlation with culture-positive cases. Among 75 patients, whose CSF samples were found apparently clear on physical examination, 40 of them were tested for serum lgM antibodies against JE virus with 4 (10%) cases as JE-positive in ELISA. All bacterial isolates were 100% sensitive to ceftriaxone and ciprofloxacin except S. pneumoniae which showed 80% sensitivity to ciprofloxacin in antimicrobial susceptibility testing. Variable sensitivity pattern was noted against penicillin, ampicillin, cotrimoxazole, gentamycin and erythromycin. This limited study has revealed that clinically suspected cases of AMES can have varying etiology with JE virus is an important cause detected among patients admitted in RMCH and Ceftriaxone is the drug of choice for bacterial meningitis. TAJ 2009; 22(1): 216-222